A numerical method for determining the fatigue strength of welded joints with a significant improvement in accuracy. (2018) - Lener, G.; Lang, R.; Ladinek, M.; Timmers, R.
Abstract: Modelling fatigue assessments for welded components is a challenging task as to achieving accurate results. Several influence factors reduce accuracy and often the difference between the calculated and the effective fatigue life is located in the range of factor 10 and above. This conference paper presents two advanced methods which allow the achievement of better accuracy. The main aspect consists in taking the geometry into account, a procedure that leads, though, to the need of adapting the existing methods for fatigue assessment. One of these advanced methods is used to examine a detail which has been welded with different welding processes and on different positions.